Performance comparison between Archimedean and Equiangular spiral antenna - Ibrahim Ooi, Norsyahriani; Mohamad, Sarah Yasmin; Islam, Md. Rafiqul; Hasbullah, Nurul Fadzlin (2017)
Spiral antennas are commonly used in communication systems due to their compact size, wide bandwidth and circularly-polarized radiation. This paper shows the design, simulation and analysis of two different types of spiral antenna; the Archimedean and Equiangular spiral. The spirals were designed to be working in the frequency range of 1–4 GHz using the CST Microwave Studio (CST MWS) software. These spiral antennas were designed and analyzed in two conditions; with and without a ground plane. Performance comparisons between the spirals were analyzed in terms of active region, current distribution, return loss S11, gain and radiation pattern.